Pengaruh Motivasi Belajar dan Kemampuan Pemecahan Masalah terhadap Prestasi Belajar Ekonomi Siswa Kelas XI IPS SMA Negeri 18 Medan dengan Kemandirian Belajar sebagai Variabel Intervening - Joan Christin Simbolon; Putri Kemala Dewi Lubis (Universitas Cokroaminoto Palopo, 2026)
This study was conducted in response to the low economics learning achievement of eleventh-grade social science students at SMA Negeri 18 Medan, where many students had not yet reached the minimum mastery criterion. The study aimed to examine the direct and indirect effects of learning motivation and problem-solving ability on economics learning achievement through learning independence as an intervening variable. This research employed a quantitative approach with an ex post facto design. The population consisted of 107 eleventh-grade social science students, and all students were selected as the sample using a total sampling technique. Data were collected through observation, questionnaires, and documentation of students’ economics scores. The questionnaire data were measured using a Likert scale. Data were analyzed using descriptive statistics, classical assumption tests, multiple regression, path analysis, and Sobel test with the assistance of IBM SPSS Statistics. The results showed that learning motivation and problem-solving ability had positive and significant effects on learning independence. Learning motivation, problem-solving ability, and learning independence also had positive and significant effects on economics learning achievement. In addition, learning independence was found to partially mediate the effects of learning motivation and problem-solving ability on economics learning achievement. These findings indicate that students with stronger learning motivation and better problem-solving ability tend to develop higher learning independence, which supports better economics learning achievement. The practical implication of this study is that economics teachers should strengthen active and contextual learning through problem-based tasks, independent assignments, learning reflection, and guided problem-solving activities. In conclusion, learning motivation, problem-solving ability, and learning independence are important internal factors that need to be developed together to improve students’ economics learning achievement.